Ab initio study and assignment of electronic states in molecular RaCl. (July 2021) - Isaev, T.A.; Zaitsevskii, A.V.; Oleynichenko, A.; Eliav, E.; Breier, A.A.; Giesen, T.F.; Garcia Ruiz, R.F.; Berger, R.
Highlights: Electronic structure of RaCl is studied with relativistic Fock-space coupled cluster method. Based on the computed level energies, a reassignment of previously reported levels is proposed. We found a favourable situation for laser cooling of RaCl, according to computed potential energy surfaces for the energetically lowest electronic states. A number of molecular P-odd and P, T-odd properties in the framework of a quasirelativistic zeroth-order regular approach is calculated. Abstract: Radium compounds have attracted recently considerable attention due to both development of experimental techniques for high-precision laser spectroscopy of molecules with short-lived nuclei and amenability of certain radium compounds for direct cooling with lasers. Currently, radium monofluoride (RaF) is one of the most studied molecules among the radium compounds, both theoretically and recently also experimentally. Complementary studies of further diatomic radium derivatives are highly desired to assess the influence of chemical substitution on diverse molecular parameters, especially on those connected with laser cooling, such as vibronic transition probabilities, and those related to violations of fundamental symmetries. In this article high-precision ab initio studies of electronic and vibronic levels of diatomic radium monochloride (RaCl) are presented. Recently developed approaches for treating electronic correlation with Fock-space coupled cluster methods are applied for this purpose. Theoretical results are compared to an early experimental investigation by Lagerqvist and used to partially reassign the experimentally observed transitions and molecular electronic levels of RaCl. Effective constants of P -odd hyperfine interaction W a and P, T -odd scalar-pseudoscalar nucleus-electron interaction W s in the ground electronic state of RaCl are estimated within the framework of a quasirelativistic Zeroth-Order Regular Approximation approach and compared to parameters in RaF and RaOH.